Social support, self-esteem, and happiness among undergraduate counseling students in Malaysia - Eng Su Yin @ Vivian Lim Silva (2023)
This study aimed to explore the relationship between social support, self-esteem, and happiness among undergraduate counseling students in Malaysia. A quantitative survey was conducted using random sampling on 299 undergraduates from a public university in Malaysia. The results of the study showed that social support on average score is high, as well as the self-esteem level among counseling students in Malaysia and happiness score is high. Pearson correlation analyses revealed significant positive relationships between social support and happiness and between self-esteem and happiness. There was also a significant positive correlation between social support and self-esteem. The study further examined the mediating role of self-esteem between social support and happiness using regression analysis, and the results showed that self-esteem mediated the influence of social support on happiness. Understanding the dynamics of these variables can provide valuable information to body knowledge, educators, cousnelor and policymakers to support and nurture the well-being of undergraduate counselling students in Malaysia.